(untitled) (Altre Modernità, 2019)
This essay explores the way two languages typically considered “less-common” can be connected through creative composition, translation and interpretation. Working together in a course on Great Lakes History at the University of Wisconsin-Milwaukee, three co-authors confront the problem of creating culturally informed translations of two indigenous texts. One author is the professor of the course and an Anishinaabe poet sharing her own work with students. One author is a writer and sign-language interpreter. One author is a long-distance Anishinaabe cultural consultant. In the class, students learn to read and recite two texts originally composed in Anishinaabemowin and translated into English. With Deaf students enrolled in the course, an additional translation into American Sign Language (ASL) is needed. An ASL interpretation of each text based only on the English translation is useful, but does not contain the full meaning of the Anishinaabemowin original. Together the team created an ASL version which reflects more detail and cultural nuances. The primary aim of this essay is to demonstrate a method for reducing audism by using inter-cultural methodologies to produce more accurate translations and decolonial and deaf-centric interpretations. A secondary aim of the essay is to compare and contrast Anishinaabemowin and ASL leading to the suggestion that more work should be done to directly connect indigenous and sign languages.